1985
DOI: 10.1002/ana.410180305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical history, brain metabolism, and neuropsychological function in Alzheimer's disease

Abstract: Data concerning 7 patients with a diagnosis of presumptive Alzheimer's disease (mean age, 65.6 years) are presented in detail in relation to the patients' regional cerebral metabolic rates for glucose. Rates were measured by positron emission tomography with fluorine 18-labeled fluoro-2-deoxy-D-glucose under conditions of reduced visual and auditory stimulation. A relationship was found between severity of dementia and brain metabolism. In patients with mild to moderate Alzheimer's disease, memory and intellec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…That is, in those patients in whom cognitive function and anterior cortical regions are most im-paired, the lateral temporal and occipital cortices show higher relative metabolism. This finding is not unlike that of Cutler et al (1985), who found high relative occipital FDG metabolism in the most severe AD cases, and is consistent with neuropathological sparing of the occipital cortex (Brun and Englund, 1981). Our findings suggests that there may also be relative sparing of lateral temporal cortex in early AD.…”
Section: Discussionsupporting
confidence: 80%
“…That is, in those patients in whom cognitive function and anterior cortical regions are most im-paired, the lateral temporal and occipital cortices show higher relative metabolism. This finding is not unlike that of Cutler et al (1985), who found high relative occipital FDG metabolism in the most severe AD cases, and is consistent with neuropathological sparing of the occipital cortex (Brun and Englund, 1981). Our findings suggests that there may also be relative sparing of lateral temporal cortex in early AD.…”
Section: Discussionsupporting
confidence: 80%
“…Although there is no consensus on the most suitable reference region for normalization of SUVs for intersubject comparison of 18 F-FDG scans, the cerebellar cortex has been widely utilized. The metabolism of cerebellar cortex has been shown to be relatively unaffected in mild-tomoderate AD (1,28,29), though significant hypometabolism has been reported in severe AD (30).…”
Section: Discussionmentioning
confidence: 99%
“…Standardized regional quanti tation was achieved using an interactive mapping pro gram (Herholz et aI., 1985). A categorical region matching and block shifting procedure (Pawlik et aI., 1986) provided optimal comparability both among sub- (Ferris et al, 1980;Benson et al, 1983;De Leon et al, 1983;Friedland et al, 1985;Cutler et al, 1985).…”
Section: Methodsmentioning
confidence: 99%